From Assistance to Over-Reliance: Rethinking ChatGPT’s Role in Grammar Learning - Alqahtani, Fatmah A.; Abumalik, Asma Mohammed (Forum for Linguistic Studies, 2025)
This study examines a notable trend among language learners: their reliance on ChatGPT bots for generating grammatical information. The use of these tools reflects a positive response to advancements in technology. While the study acknowledges the benefits of ChatGPT in facilitating learning for both teachers and students, it also addresses a critical concern: the accuracy of the information provided by these bots. Some students may assume that the information from ChatGPT is always reliable, leading to an over-reliance on its outputs, particularly regarding grammatical concepts.To investigate this issue, the study analyzed 12 randomly selected ChatGPT bots, each responding to a grammatical query. The results revealed a concerning lack of accuracy, with scores ranging from 0% to 80%, and none achieving a perfect score of 100%. To further understand user awareness of these limitations, two questionnaires were distributed to language instructors and learners. While both groups recognized the utility of ChatGPT, instructors expressed significant concern over students’misconceptions and their over-reliance on these tools. Acknowledging the limitations of ChatGPT, instructors are actively warning their students about those limitations, which is crucial for their effective learning. Given that learners often feel confident in ChatGPT’s reliability, educators need to establish guidelines for its appropriate use in the classroom to mitigate over-reliance. Additionally, experts in various fields could provide references and resources that enhance the accuracy of information generated by such tools, making them more valuable for users across different specialties.